City Self-Government in Russia at the End of XIX - XXI Centuries: Processes of Decentralization and Internal Structuring - O. A. Polyanina (Научный диалог)
The article is devoted to the problem of decentralization of urban self-government in Russia in the XIX - early XXI centuries. Both the practical experience of functioning of intra-urban municipalities (small urban units), and the level of theoretical understanding of the problems of decentralization in different periods of national history are analyzed in the article. The author has identified three time periods when the idea of creating a small city unit took on practical implementation: the revolutionary period in 1917-1918, the decade from 1995 to 2005 and the period from 2014 to the present. The author considers the socio-political context of the transformation at each of these stages. Particular attention is paid to the transformation of the regulatory framework in the studied area. It is shown that the legislation alternately ruled out, then allowed the possibility of creating intra-city municipalities, which impeded the progressive development of this level of municipal authority. The scientific novelty of the work is in the fact that the author revealed common typological features of the decentralization process that are characteristic of all the stages studied. It is concluded that the relatively low efficiency of a small urban unit is due to the politicization of its problems and the lack of historical continuity.